Treatment of Bullous Pemphigoid with Avdoralimab: Multicenter, Randomized, Open-Labeled Phase 2 Study - Thierry Passeron; Eric Fontas; Thierry Boye; Marie-Aleth Richard; Emmanuel Delaporte; Olivier Dereure (Elsevier, 2024)
Rationale: Experimental data support the role for C5a-C5aR1 axis activation in bullous pemphigoid. We assessed the efficacy and safety of avdoralimab, a specific anti-C5aR1 mAb, for treating bullous pemphigoid. Methods: We conducted a phase 2 open-labeled randomized multicenter study. Patients with proven bullous pemphigoid were randomized (1:1) to receive superpotent topical steroids alone (group A) or with avdoralimab (group B). All patients received 0.05% clobetasol propionate cream until 15 days after the healing of lesions. Patients in group B additionally received 3 injections of avdoralimab every week for 12 weeks. The main criterion of evaluation was the proportion of patients with initial control of disease activity still in complete clinical remission at 3 months with no relapse during the study period. Results: Fifteen patients were randomized: 7 to group A and 8 to group B. Two patients in group A and in group B achieved control of disease activity at week 4. Only 1 patient was still in complete clinical remission at week 12 in group B, and none was in group A. No adverse event related to the treatment was reported. Conclusions: This proof-of-concept pilot study did not show preliminary signal of additional avdoralimab efficiency compared with superpotent topical steroids alone.